Head rotation influences the geometric features of the stenotic carotid bifurcation - Brott, Brigitta C.; Aristokleous, Nicolas; Seimenis, Ioannis; Papaharilaou, Yannis; Eracleous, Eleni A.; Georgiou, Georgios C.; Anayiotos, Andreas (My University, 2012)
Previous investigators have reported that posture changes may influence the geometry and hemodynamics of the carotid bifurcation [1,2]. As a result, head rotation may cause geometric changes that alter the hemodynamic variables previously cited to correlate with the development of atherosclerosis. Glor et al. [1] had reported changes in the right carotid bifurcation geometry with leftward rotation of the head. Aristokleous et al. [2] have reported that geometric differences in the right and left carotid bifurcation occur with a rightward rotation of the head in 10 healthy volunteers [2]. Also, a similar study on bilateral head rotation on the left and right carotid bifurcation of two volunteers has shown similar results [3]. In this study a group of four patients with atherosclerotic disease in the carotid arteries was investigated at two head postures, a) the supine neutral and b) the prone sleeping with head rotation leftwards up to 80° to investigate the level of stenosis and the changes in geometric parameters with head rotation.
Keywords: Carotid bifurcation; Hemodynamic; Carotid bifurcation